2017
DOI: 10.1002/app.44898
|View full text |Cite
|
Sign up to set email alerts
|

Surface grafting of poly(pentafluorostyrene) on the iron and iron oxide particles via reversible addition fragmentation chain transfer (RAFT) polymerization

Abstract: A surface grafting technique is reported for synthesis of poly(pentafluorostyrene) via reversible addition fragmentation chain transfer onto iron (iron oxide) particles. 4-Methoxydithiobenzoate is used for the RAFT chain transfer agent. The molecular weight, surface morphology, thickness, thermal properties, and monomer conversion of the grafted polymer are reported. The grafted poly(pentafluorostyrene)-iron particles show a higher thermal transition temperature compared to the nongrafted polymer because it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Comparing the remaining weight % of SiNP-CPDB with that of pPFS- g -SiNP samples (P1 to P5) at 700 °C, it is found that the amount of FPB grafting increases gradually with the increase in chain length from P1 to P5, which is in good correlation with the trend seen in the case of GPC data. A major weight loss at ∼410 °C is observed in the TGA curve of P1 to P5, which attributes to the degrafting of the pPFS anchors from the SiNP surface via decomposition of the pPFS backbone, and this is in accordance with the literature report. ,, Almost a similar pattern can be noticed for pPFPA- g -SiNP polymers (P6–P10) where the major weight loss occurred at ∼310 °C, and this weight loss is more prominent for polymers with higher chain lengths gradually from P6 to P10 attributing to the degradation of the pPFPA polymer backbone. It has also been noted that with the increase in monomer feed ratio, the polymer chain grafting density (σ) also increases gradually from P1 to P5 and P6 to P10 (Table ).…”
Section: Results and Discussionsupporting
confidence: 90%
“…Comparing the remaining weight % of SiNP-CPDB with that of pPFS- g -SiNP samples (P1 to P5) at 700 °C, it is found that the amount of FPB grafting increases gradually with the increase in chain length from P1 to P5, which is in good correlation with the trend seen in the case of GPC data. A major weight loss at ∼410 °C is observed in the TGA curve of P1 to P5, which attributes to the degrafting of the pPFS anchors from the SiNP surface via decomposition of the pPFS backbone, and this is in accordance with the literature report. ,, Almost a similar pattern can be noticed for pPFPA- g -SiNP polymers (P6–P10) where the major weight loss occurred at ∼310 °C, and this weight loss is more prominent for polymers with higher chain lengths gradually from P6 to P10 attributing to the degradation of the pPFPA polymer backbone. It has also been noted that with the increase in monomer feed ratio, the polymer chain grafting density (σ) also increases gradually from P1 to P5 and P6 to P10 (Table ).…”
Section: Results and Discussionsupporting
confidence: 90%
“…We divide this approach into two well-known methods such as “grafting from” and “grafting to”. The method of “grafting from” was widely used to decorate the surface of silica wafers or nanoparticles. ,, This method allows good control of the grafting density but needs strict reaction conditions and modification of the surface before polymerization. , Although, most of the publications report on the use of controlled radical polymerization to produce the desirable properties of the shell, these methods are difficult to scale up for industrial applications. ,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…20,21 Although, most of the publications report on the use of controlled radical polymerization to produce the desirable properties of the shell, these methods are difficult to scale up for industrial applications. 15,22,23 SiO 2 nanoparticles grafted with poly(ethylene oxide) chains were successfully used as a solid polymer electrolyte (SPE) in the Li-metal−polymer battery. This material exhibited a remarkable ionic conductivity of 1.2 × 10 −3 S cm −1 at 60 °C.…”
mentioning
confidence: 99%
“…To date, over hundreds of reviews have been published involving in RAFT polymerization, covering a tremendous amount of polymer synthesis and applications, in terms of architectures (block, star, hyperbranched, cross-linked) [ 25 , 26 , 27 , 28 , 29 ], surface-grafted (inorganic nanocomposites, 2D graphene) [ 30 , 31 , 32 ] and functionalities (stimuli-responsive, biodegradable) [ 33 , 34 , 35 , 36 ]. In these studies, optoelectronic functional materials by RAFT polymerization have been widely investigated for their wide application prospect.…”
Section: Introductionmentioning
confidence: 99%